2005
DOI: 10.1002/ijc.21207
|View full text |Cite
|
Sign up to set email alerts
|

Association of a single nucleotide polymorphism in the matrix metalloproteinase‐1 promoter with glioblastoma

Abstract: A key feature in the malignant behavior of glioblastoma is the tendency to invade host brain tissue surrounding the primary tumor site. Several members of the matrix metalloproteinase family are thought to contribute to this invasive capacity. A single nucleotide polymorphism has been described in the matrix metalloproteinase-1 (MMP-1) promoter that consists of either the presence or absence of a guanine nucleotide at position 21607. The presence of the guanine base creates a functional binding site for member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 27 publications
3
24
0
1
Order By: Relevance
“…We have demonstrated that ETS1 activates this region of the promoter in chondrocytes (Fig. 6C), and previous reports have shown that ETS and AP-1 factors bind to this site as part of a large protein complex (56,65,74,77). Our results indicate a functional antagonism between NURR1 and ETS1, where NURR1 reduces ETS1 induction of the MMP-1 promoter, and ETS1 blocks transactivation of the NBRE reporter (Fig.…”
Section: Volume 282 • Number 13 • March 30 2007supporting
confidence: 82%
“…We have demonstrated that ETS1 activates this region of the promoter in chondrocytes (Fig. 6C), and previous reports have shown that ETS and AP-1 factors bind to this site as part of a large protein complex (56,65,74,77). Our results indicate a functional antagonism between NURR1 and ETS1, where NURR1 reduces ETS1 induction of the MMP-1 promoter, and ETS1 blocks transactivation of the NBRE reporter (Fig.…”
Section: Volume 282 • Number 13 • March 30 2007supporting
confidence: 82%
“…The haplotypes also reflect the previously described linkage disequilibrium between the MMP-1 2G allele and the MMP-3 5A allele (40). Polymorphisms in the promoters of MMPs have a functional role and have been shown to exhibit allelotypic effects on levels of gene transcript (15,32). Although the lifelong effects of altered transcription are unclear, overexpression of MMPs caused by promoter polymorphisms may enhance cancer progression by virtue of their role in degradation of the ECM, thereby generating an environment that favors tumor cell migration.…”
Section: Discussionsupporting
confidence: 62%
“…However, macrophages produce and release a factor VII-like protein that activates factor X (Shands, 1983(Shands, , 1985Tsao et al, 1984). Several reports suggest that MMP1 and factor X can be made by microglia and astrocytes (Nakagawa et al, 1994;Yamada and Nagai, 1996;Shikamoto and Morita, 1999;Ghorpade et al, 2001;Lorenzl et al, 2002Lorenzl et al, , 2004Gardner and Ghorpade, 2003;Kunapuli et al, 2004;Hamill et al, 2005;McCready et al, 2005). In addition, there is strong evidence that prothrombin, the precursor to thrombin, is expressed throughout the CNS (Soifer et al, 1994;Weinstein et al, 1995).…”
Section: Discussionmentioning
confidence: 99%